Comparison of two methods of seminal plasma removal on buffalo (Bubalus bubalis) sperm cryopreservation. (19th May 2017) - Albuquerque, RS; Morais, R; Reis, AN; Miranda, MS; Dias, EAR; Monteiro, FM; Paz, CCP; Nichi, M; Kawai, GKV; Della'Aqua, CPF; Papa, FO; Viana, RB; et al.
Contents: Cryopreservation causes damage to spermatozoa, and methods minimizing this damage are therefore needed. Although much discussed, seminal plasma removal has become an alternative to improve sperm quality and viability after freezing and has been applied to different species in attempt to obtain good results. The objective of this study was to evaluate semen quality in buffaloes submitted to two methods for seminal plasma removal (filtration and centrifugation). Semen samples were collected from seven Murrah buffalo bulls ( Bubalus bubalis ) once a week for 8 weeks. Each ejaculate was divided into three groups: control (presence of seminal plasma), centrifugation and filtration. Sperm kinetics was evaluated with the computer‐assisted sperm analysis (CASA) system. Plasmalemma and acrosomal membrane integrity, mitochondrial membrane potential and reactive oxygen species (ROS) were measured by flow cytometry, and lipid peroxidation was evaluated by the thiobarbituric acid reactive substances (TBARS) assay. Seminal plasma removal did not improve sperm kinetics compared to the control group. Centrifugation increased the number of cells with damaged acrosomal membranes (0.77 ± 0.05) and filtration caused greater plasmalemma and acrosomal membrane damage (22.18 ± 1.07). No difference in the mitochondrial membrane potential was observed between groups. In contrast, ROS production was higher in the centrifugation group compared to the control and filtration groups, although no differences in TBARS formation were detected. In conclusion, seminal plasma removal did not improve the quality of thawed buffalo semen compared to control in terms of sperm kinetics, membrane integrity, mitochondrial membrane potential or lipid peroxidation.